지역사회획득 폐렴의 치료지침 권고안 - 송재훈; Jae Hoon Song; 정기석; Ki Suck Jung; 강문원; Moon Won Kang; 김도진; Do Jin Kim; 배현주; Hyun Joo Pai; 서지영; Gee Young Suh; et al. (Tuberculosis and respiratory diseases, 2009)
The successful treatment of community-acquired pneumonia requires appropriate, empirical antimicrobial therapy. The etiology and antimicrobial susceptibility of major pneumonia pathogens can differ by country. Therefore, the ideal treatment guidelines for community-acquired pneumonia should be based on the studies performed in each country. We developed a treatment guideline for community-acquired pneumonia for immunocompetent adults in Korea. This guideline was developed by the joint committee of the Korean Society for Chemotherapy, the Korean Society of Infectious Diseases, and the Korean Academy of Tuberculosis and Respiratory diseases.